Environmental Governance in Hungary - Rural Development Policies and Social Learning during the Implementation of EU Agri-Environmental Policies - A Case Study - Gusztáv Nemes (Hungarian Academy of Sciences, Institute of Economics, 2010)
The Rural Development Regulation (RDR) within the Common Agricultural Policy (CAP), as an exemplary manifestation of the New Rural Development Paradigm, has achieved significant results. Nevertheless, it has increasingly become liable to institutional complexity and central control in an emerging system - discussed as 'the project state' or 'projectified world' in recent literature. The intersection of different institutional realities (European, domestic, regional, local, sectoral, spatial, etc.) and the resulting institutional bricolage is inevitably contested. The dispute is even more apparent in CEE countries, where multi-level governance is problematic and the New Paradigm has good possibilities, but little tradition. This case study of the implementation of the Hungarian Agri-Environmental Programme (HAEP) intends to illustrate how a disfunctioning project state (clientalism, insufficient bureaucracy, direct political influence) can distort the implementation of rural development policies. We found that the design and the implementation of the programme (HAEP) was subjected to ongoing political influence and the power struggle of three main mindsets, representing different lobbies: the agriculturalists, the green-minded and the accountability-minded actors. As a consequence, the main emphasis remains on the distribution of financial resources, thus original objectives (environmental protection and effective social learning) are not fulfilled. The case study is part of my ongoing research "Local Development Policies in a European Project State - A Systemic Analysis of Institutional Bricolage" supported by an NFM-OTKA grant.
Keywords: D73; D74; D78; H83; J18; Q00; Q01; Q18; Q19; Q51; Q56; Q58; Y80; 330; social learning; environmental governance; agri-environmental policies; CAP; EU policies; environmental protection; project state; evaluation; Umweltpolitik; Agrarpolitik; Umweltschutz; Lernprozess; EU-Agrarpolitik; EU-Umweltpolitik; Ungarn